Knowledge management in the human resources recruitment and selection process - Silva, Susana (2022)
Human resources management is related to a strategic and provisional vision of the organisations. Several authors have pointed the need to understand the human resources practices and the way different organisations implement these practices. On the other hand, it is also important how the information is managed during the several human resources practices. The main objective of the study is to understand the perception of human resources consultants during the recruitment and selection process. It also aims to understand how the recruitment and selection process is conducted, to comprehend the motivations of the recruiters during the process, to characterize the soft skills measured, and how the information is managed. In this qualitative study, participated 12 recruiters, of both genders, with mean age of 36 years (SD=7.98). The participants fulfilled a demographic questionnaire and it was conducted a semi-structured interview. Data were verbatim transcript and analysed according content analysis. The main results showed that recruiters have a positive perception of their activity. The online recruitment was identified as a source of excellency to attract candidates. Regarding to the assessment techniques the interview is the most frequent technique used during a recruitment and selection process therefore the competence of the recruiter conducting these interviews is pointed as very important. The recruiters referred that all the process is focused in the soft skills, and they reported a large degree of confidence in the evaluation methods used. The motivation of the recruiters lies essentially in the scope of knowledge of their function and development opportunities. Thus, it can be concluded that recruitment and selection is a very complex process with several features and all the information related to these processes should be managed very carefully. We discuss the main practical and theoretical implications, and offer some suggestions for further studies.